ANALYZING THE HISTORY AND SOCIAL VALUES OF THE KELAYAN MUHAMMADIYAH MOSQUE: Menganalisis Sejarah dan Nilai-Nilai Sosial Dari Keberadaan Masjid Muhammadiyah Kelayan - Muhammad Rico; Herry Porda Nugroho Putro; Syaharuddin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Banjarmasin is a city where the majority of the population is Muslim, this is proven by the many mosques that are hundreds of years old. One of the mosques which stands on Jalan Kelayan B Banjarmasin is not only a place of worship but also a social center with the existence of BPK MMK which aims to help residents, especially the South Banjarmasin sub-district. This mosque is a historic mosque beloging to the Muhammadiyah organization in the city of Banjarmasin. It has a special style for the city of Banjarmasin because the front faces the bank of the kelayan river. The Kelayan Muhammadiyah Mosques was founded 85 years ago, when there were Muhammadiyah activities in Banjarmasin, this mosque was always visited considering the history of the mosque’s founding which at that time was still during the Dutch occupation era, but the enthusiasm for building a mosque was quite high among residents around the South Banjarmasin sub-district. The research uses qualitative methods wihich are described descriptively. Data was collected from observation and in-depth interviews. Sample determination was carried out using the snowball sampling technique. The benefit of this writing is to provide information to the public that the kelayan Muhammadiyah Mosque is full of history and social values and needs to be maintained as one of the icons of the city of Banjarmasin.